2022
DOI: 10.1071/ma22050
|View full text |Cite
|
Sign up to set email alerts
|

Japanese encephalitis virus: an emerging and re-emerging virus in Australia

Abstract: Japanese encephalitis virus (JEV) first emerged in the Torres Strait of north-eastern Australia in 1995, with three human cases, and widespread infection of pigs on a number of islands. The virus was shown to belong to genotype II. Further cases occurred in 1998, including the first case on mainland Australia on Cape York. A second genotype of JEV, genotype Ia, was reported in mosquitoes and pigs in 2000-04, possibly displacing genotype II. JEV re-emerged in Australia with a fatal human case on the Tiwi Island… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Soon after JEV emerged in the mid-1990s, it was postulated that environmental conditions were suitable for the establishment of the virus on the Australian mainland [22]. However, despite at least two introductions of the virus into the region [13,20], there was no evidence to suggest this scenario eventuated [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soon after JEV emerged in the mid-1990s, it was postulated that environmental conditions were suitable for the establishment of the virus on the Australian mainland [22]. However, despite at least two introductions of the virus into the region [13,20], there was no evidence to suggest this scenario eventuated [19].…”
Section: Discussionmentioning
confidence: 99%
“…A sentinel pig program detected JEV activity every year (except 1999) in the Torres Strait between 1995 and 2005 [18,19], although identification of only genotype 1 viruses from the year 2000 onward suggested that a separate incursion of the virus into the region had occurred [20]. Activity in 1998 and 2004 spread onto Cape York Peninsula, but there was no evidence that the virus had become established in natural transmission cycles on the mainland [14,21], despite ecological conditions potentially being suitable for its establishment [22]. The status of JEV in northern Australia had become less clear, as most forms of targeted surveillance were gradually phased out after 2011 [19].…”
Section: Introductionmentioning
confidence: 99%
“…Historically, GIII was the dominantly detected strain, however it has recently been superseded by GI [25][26][27]. GII is largely confined to Southeast Asia and Northern Australia [28], and GIV and GV are generally confined to tropical Southeast Asia [29], however the 2022 outbreak of JEV in Australia was determined to be GIV, representing a range expansion of this genotype [30]. Vaccines are largely derived from GIII genotypes [29,31] and a growing body of evidence suggests that these vaccines show reduced efficacy toward GI and GV strains [32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…The mosquito-borne Japanese encephalitis virus (JEV; Orthoflavivirus japonicum) recently emerged in South-eastern Australia [1]. JEV is the major cause of human viral encephalitis in Southeast Asia, with an estimated 68,000 to 100,000 cases occurring annually [2,3].…”
Section: Introductionmentioning
confidence: 99%